Respostas
respondido por:
6
x - 3y = 1 *(-2)
2x + 5y = 13
-2x + 6y = -2
2x + 5y = 13
11y = 11
y = 11/11
y = 1
2x + 5y = 13
2x + 5*(1) = 13
2x + 5 = 13
2x = 13 - 5
2x = 8
x = 8/2
x = 4
Resposta: O valor de x é 4 e y vale 1.
2x + 5y = 13
-2x + 6y = -2
2x + 5y = 13
11y = 11
y = 11/11
y = 1
2x + 5y = 13
2x + 5*(1) = 13
2x + 5 = 13
2x = 13 - 5
2x = 8
x = 8/2
x = 4
Resposta: O valor de x é 4 e y vale 1.
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás